Nanotechnology in Oil and Gas Industries Principles and Applications - Saleh, Tawfik Abdo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides a powerful source to develop new, rapid and highly efficient materials for the application in various fields of oil and gas fields. It focuses on the synthesis, characterization and applications of various Nanomaterials, presenting the state-of-the-art in developments and innovations in nanocomposites. This book provides the complete practical and theoretical information about the synthesis of nanoparticles with potential use in the field of oil and gas.
Insights into the fundamentals and principles of the oil and gas industry: the impact of nanotechnology -- Nanotechnology Applications in Petroleum Refining -- Advances in nanocatalyzed hydrodesulfurization of gasoline and diesel fuels -- Improvement of Hydrodesulfurization Catalysts Based on Insight of Nano Structures and Reaction Mechanisms -- Selective sulfur removal from liquid fuels using nanostructured adsorbents -- Nano-MoS2 and Graphene Additives in Oil for Tribological Applications -- Hydrodesulfurization (HDS) Process Based on Nano-catalysts -- Mechanisms of desulfurization by Nanomaterials -- Role of nanomaterials as an emerging trend towards the detection of winged contaminants -- Biogas produced from different feedstocks in anaerobic digesters.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Cogeneration of electric power and heat; Fossil fuels; Nanochemistry; Catalysis; Nanotechnology; Microsystems and MEMS; Fossil Fuel; Nanochemistry; Catalysis